Research on power coupling interface in multi-technology fusion collaborative simulation under novel power system - ZOU Shirong; LU Youfei; LIANG Xueqing; LIU Chao; FENG Binjie; XU Jin (Diance yu yibiao)
After a large number of power electronic equipment is connected, the shape of the power system is constantly changing, and the traditional single simulation technology cannot cope with the complex simulation tasks of the novel power system. Collaborative simulation can realize the effective interaction between various simulation tools and can be used to simulate the specific behavior of multi-technology fusion complex systems. A new simulation interface design method is proposed in this paper. The simulation interface can couple the power network models established in different simulation tools and transfer the impedance information between the coupling systems in the simulation. The establishment process of collaborative simulation platform and the interactive protocol of collaborative simulation are given. The traditional V-I interface method and transmission line interface method are analyzed, the interface impedance is parameterized to get a general simulation interface, and it is proved that the traditional V-I method and transmission line method can be regarded as their special cases. It shows how to analyze the simulation stability through the interface passivity, and solve the simulation accuracy problem based on the concept of interface transparency. The actual performance of the proposed interface design method is demonstrated by three simulation scenarios, including 118-node reference network, reference network connected to static reactive power compensator and reference network connected to wind farm. The simulation results show that the proposed interface design method can effectively connect different simulation software and has higher accuracy while maintaining stability.